Presence of tophi and carotid plaque were risk factors of MACE in subclinical artherosclerosis patients with gout: a longitudinal cohort study - Wang, Yu; Deng, Xuerong; Zhang, Xiaohui; Geng, Yan; Ji, Lanlan; Song, Zhibo; Zhang, Zhuoli (Frontiers in Immunology, 2023)
Background: Patients with gout carry an excess risk for cardiovascular disease (CVD), but the contribution of subclinical arthrosclerosis to CVD risk and events has never been reported. In this study, we aimed to explore the predictive factors for incident major adverse cardiac events (MACE) in gouty patients without previous history of CVD or cerebral vascular disease. Methods A single-center, cohort analysis was performed to assess subclinical atherosclerosis at baseline since 2008. Patients were excluded if they had previous diagnosed CVD or cerebral vascular disease. The outcome of study was first MACE. The presence of subclinical atherosclerosis was assessed by carotid plaque (CP) and carotid intima-media thickness (CMIT) was determined by ultrasound. Ultrasound scan of bilateral feet and ankles was performed at baseline. The association between tophi, measurements of carotid atherosclerosis and risk of developing incident MACE was evaluated using Cox proportional hazards models, with adjustment for the CVD risk scores. Results A total of 240 consecutive patients with primary gout were recruited. Their mean age was 44.0 years with male predominant (240, 99.2%). During a median follow-up of 10.3 years, incident MACE was ascertained in 28 (11.7%) patients. In a cox hazards model, which controlled for the CV risk scores, at least 2 tophi (HR 2.12-5.25, P<0.05) and carotid plaque (HR 3.72-4.01, P<0.05), were both independent predictor of incident MACE in gouty patients separately. Conclusions The presence of at least 2 tophi and carotid plaque on ultrasound could independently predict MACE in addition to conventional cardiovascular risk factors in gouty patients.